O trabalho formativo do coordenador pedagógico junto aos professores que ensinam matemática - Langona, Neichelli Fabrício (Universidade Federal de São Carlos, 2017)
The present study has as general objective to analyze the dimensions and centrality of the work developed by the pedagogical coordinators in the continuing formation in service of teachers who teach mathematics in the initial years of Elementary School in the Municipal Network of education of a city in the interior of the state of. This objective is broken down into three other specific objectives: (i) identify the responsibilities of the pedagogical coordinator; (ii) to select and analyze training proposals developed by the pedagogical coordinators on mathematics teaching; and (iii) seek, together with the pedagogical coordinators, the challenges and possibilities of formative work for the teaching of mathematics. For this, the research was qualitative and interpretative, using as a tool the first stage of the data collection a mixed questionnaire, offered to all the coordinators of the initial years of Elementary School of the municipal network. In the second stage of data collection, used and triangulated three instruments (questionnaire, interview and training projects) of two coordinators. For the analysis of the data we find the theoretical contribution referring to the work of the pedagogical coordinator, the formative work performed by this professional, authors who defend the school as a space of continuous formation, teacher training and about the teacher who teaches mathematics. As a result, we verified that the pedagogical coordinator has four different natures that correspond to the teaching and learning processes, school organization, democratic and participatory environment, and teacher training.
The training work of the pedagogical coordinator to teachers who teach mathematics
Keywords: Atuação do coordenador pedagógico; Formação continuada de professores que ensinam matemática; Projetos de Formação; Teaching coordinator performance; Continuing education of teachers teaching Mathematics; Training Projects; Professores - Formação; Matemática - Estudo e ensino; Teachers - In-service training; Mathematics - Study and teaching; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO